2013
DOI: 10.1007/s11661-013-1912-7
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Growth Morphologies in Al-Zn Alloys—Part I: X-ray Tomographic Microscopy

Abstract: Upon solidification, most metallic alloys form dendritic structures that grow along directions corresponding to low index crystal axes, e.g., h100i directions in fcc aluminum. However, recent findings [1,2] have shown that an increase in the zinc content in Al-Zn alloys continuously changes the dendrite growth direction from h100i to h110i in {100} planes. At intermediate compositions, between 25 wt pct and 55 wt pct Zn, h320i dendrites and textured seaweeds were reported. The reason for this dendrite orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Prior studies have observed seaweed-like structures during solidification either at near-isothermal conditions [24][25][26][27] or in deeply undercooled metallic melts. [28][29][30] Textured seaweed structures were also observed by Rappaz et al [8][9][10]19] in aluminum alloys when zinc was added at compositions of 25 to 55 wt pct. Our results in Mg-Zn, combined with those of Rappaz et al in Al-Zn, support Rappaz's hypothesis that the increase in interfacial energy anisotropy due to the addition of Zn alters the growth morphology.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Prior studies have observed seaweed-like structures during solidification either at near-isothermal conditions [24][25][26][27] or in deeply undercooled metallic melts. [28][29][30] Textured seaweed structures were also observed by Rappaz et al [8][9][10]19] in aluminum alloys when zinc was added at compositions of 25 to 55 wt pct. Our results in Mg-Zn, combined with those of Rappaz et al in Al-Zn, support Rappaz's hypothesis that the increase in interfacial energy anisotropy due to the addition of Zn alters the growth morphology.…”
supporting
confidence: 59%
“…Understanding and controlling microstructural evolution in Mg alloys, including dendritic growth orientation and morphology during solidification, is critical to obtaining optimal mechanical properties. [4] Microtomography has proven to be a powerful tool for investigating dendritic growth and morphology for bcc and fcc alloys, with prior studies primarily focussed on binary aluminum alloys containing copper [5][6][7] or zinc, [8][9][10] which grow with a preferred orientation of [100] and form a four-fold symmetric structure. [4,11] Mg alloys are hcp, with a crystal structure that has six-fold symmetry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…IN a companion article, [2] X-ray tomographic microscopy was used to characterize the microstructures that form in directionally solidified (DS) and quenched Al-Zn alloys for various Zn compositions ranging from 5 to 90 wt pct. The results obtained in that study were in agreement with those previously found by Gonzales and Rappaz [3,4] on DS (but not quenched) Al-Zn alloys.…”
Section: Introductionmentioning
confidence: 99%